Pembuatan Briket Biomassa Berbahan Baku Kulit Pisang Kepok dan Kulit Pisang Raja dengan Aditif Tempurung Kelapa - Rahmadita, Ahmad Fata (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
Energy sources that promise to replace our dependence on fossil fuels include biomass waste sources. This study studied the characteristics of biobriquettes from variations of kapok banana peels plus coconut shells and variations of plantain peels added coconut shells with variations in the addition of tapioca adhesive. This study was designed with fixed variables of variation in raw material composition with a sample of 90:10; 80:20; 70:30 (grams) and tapioca adhesive composition 10; 20; 30; 40; 50 (%). Banana peels that have dried naturally are then carbonized with a temperature of 300°C -350°C for 3 hours. The process of making biobriquettes begins with the crushing of charcoal and filtering charcoal grains so that a grain size of 60 mesh is obtained. Then the charcoal is mixed between kapok banana peel charcoal and plantain with coconut shell charcoal with a variation of 90:10; 80:20; 70:30 (grams) then the variation of the charcoal mixture is mixed with tapioca flour as an adhesive with variation 10; 20; 30; 40; 50 (%). Then formed biobriquette dough, then molded with a pressure of 100 kg / cm2 and dried under the hot sun. Furthermore, the charcoal is characterized by 5 parameters, namely moisture content, ash content, bound carbon content and calorific value test and compressive test. The best results for banana kepok obtained from this study were in a sample of a mixture variation of 70:30 grams with a variation of a 20% tapioca adhesive mixture. With a moisture content value of 6.95%, ash content of 16.6%, bound carbon content of 60.45%, calorific value of 6,539.04 cal/g and a compressive test value of 86.98 kg/cm2. The best results for plantains obtained from this study were in samples of mixed variations of 70:30 grams with variations of tapioca adhesive mixtures of 50%. With a moisture content value of 7.09%, ash content of 15.8%, bound carbon content of 62.31%, calorific value of 5,415.14 cal/g and a compressive test value of 89.69 kg/cm2. The results obtained in this study for water content, ash content and bound carbon content have not met, then for calorific values and compressive tests have met SNI 01-6235-2000 standards, which are ≥ 5,000 cal / g.